2019
DOI: 10.1101/512632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microtubule plus-end dynamics link wound repair to the innate immune response

Abstract: As a first line of defence against the environment, the epidermis protect animals from infection and physical damage. In C. elegans, wounding the epidermal epithelium triggers both an immune reaction and a repair response. Exactly how these are controlled, and the degree to which they are inter-connected remains unclear. To address these questions, we established a simple system for simultaneously inflicting precise laser wounds and imaging at high spatial and temporal resolution. We show that in C. elegans, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 60 publications
5
24
0
Order By: Relevance
“…Upon infection, SNF-12 plays an essential role in the induction of AMPs, through its interaction with STA-2 (Dierking et al, 2011). We recently demonstrated that upon wounding, SNF-12 is recruited to the injury site, in a microtubule dependent manner (Taffoni et al, 2020) and that this is crucial for AMP gene expression. Thus DcEntA may inhibit AMP gene expression indirectly through an effect on SNF-12 localisation and activity.…”
Section: Discussionmentioning
confidence: 99%
“…Upon infection, SNF-12 plays an essential role in the induction of AMPs, through its interaction with STA-2 (Dierking et al, 2011). We recently demonstrated that upon wounding, SNF-12 is recruited to the injury site, in a microtubule dependent manner (Taffoni et al, 2020) and that this is crucial for AMP gene expression. Thus DcEntA may inhibit AMP gene expression indirectly through an effect on SNF-12 localisation and activity.…”
Section: Discussionmentioning
confidence: 99%
“…pSO21 was obtained by insertion of the promoter of col-62 which is only expressed in the adult in the epidermis into the pNP154 vector. pNP154 was made from a vector containing the SEC for single insertion on Chromosome II at the position of ttTi5605 (pAP087, kindly provided by Ari Pani) (Taffoni et al 2020). pNP160 and pSO21 were injected in rde-1(ne300) at 10 ng/µl together with pDD122 (eft-3p::Cas9) at 40 ng/µl, pCFJ90…”
Section: Construction Of New Tissue-specific Rnai Strainsmentioning
confidence: 99%
“…For intestine-specific RNAi, we used the mtl-2 promotor to rescue rde-1 in the rde-1(ne300) strain (Pujol et al 2008). For epidermis-specific RNAi, we used the col-62 promoter, which is expressed from the L4 stage onward, to rescue rde-1 in the rde-1(ne300) strain (Taffoni et al 2020). To confirm the intestine-specific RNAi knockdown, we used RNA corresponding to the act-5 gene, which encodes an essential actin known to be expressed in the intestine (MacQueen et al 2005).…”
Section: Construction Of New Tissue-specific Rnai Strains For Intestimentioning
confidence: 99%
“…This reduced complexity can be advantageous for dissecting its mechanisms [26,27]. Besides pathogen infection, immune pathways in C. elegans can also be triggered by sterile injury of the epidermis [28][29][30][31]. Surveillance systems detect the presence of molecular patterns associated with physical damage, pathogens, and the cellular perturbation that they cause.…”
Section: Elegans Sleepmentioning
confidence: 99%
“…This suggests that the EGF signaling pathway is not the only pathway that signals damage, but that the innate immune pathway might increase sleep through NLP and CNC release following infection or wounding. We tested this hypothesis by wounding the cuticle and epidermis of adult worms with either a needle or a UV laser [28,30]. We then placed the worms into microfluidic chambers and followed sleep behavior and RIS depolarization using fluorescence microscopy.…”
Section: Wounding Signals Through Nlps and Cncs To The Nervous Systemmentioning
confidence: 99%